2021 IEEE International Symposium on Circuits and Systems (ISCAS) 2021
DOI: 10.1109/iscas51556.2021.9401798
|View full text |Cite
|
Sign up to set email alerts
|

Compute-in-eDRAM with Backend Integrated Indium Gallium Zinc Oxide Transistors

Abstract: With rapid growth in data intensive applications, there is an ever-increasing need for energy efficient machine learning/AI hardware accelerators. The performance and the energy efficiency of such accelerators are primarily limited due of massive amount of data movement between processing engines and the off-chip memory. This memory wall bottleneck can be mitigated by performing accelerator specific computations in the memory (CIM) array embedded with the rest of the logic blocks. Multiple embedded memory tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Therefore, these offer the advantage of improved performance at the cost of lesser retention time. To further improve the retention time and reduce the leakage of eDRAMs, few novel materials based devices like Indium Gallium Zinc Oxide eDRAMs have been proposed, which have extreme low leakage with moderate ON currents have been proposed [18,19].…”
Section: T1cmentioning
confidence: 99%
“…Therefore, these offer the advantage of improved performance at the cost of lesser retention time. To further improve the retention time and reduce the leakage of eDRAMs, few novel materials based devices like Indium Gallium Zinc Oxide eDRAMs have been proposed, which have extreme low leakage with moderate ON currents have been proposed [18,19].…”
Section: T1cmentioning
confidence: 99%
“…As an alternative, several studies have suggested PIM approaches based on embedded dynamic RAM (eDRAM) [16][17][18][19]. Compatible with general logic processes, eDRAM provides higher integration and smaller area compared to those of SRAM [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, eDRAM can be implemented in any CMOS process without the use of an additional layer. To overcome these limitations, PIMs with embedded dynamic random-acc memory (eDRAM) have been proposed [11][12][13]. Logic-compatible eDRAMs [14][15][16][17] c offer a higher bit density and smaller area than those of the SRAMs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, process-independent retention time extension is required without the use of an additional capacitor in the eDRAM gain cell. To overcome these limitations, PIMs with embedded d memory (eDRAM) have been proposed [11][12][13]. Logic-compatib offer a higher bit density and smaller area than those of the SRAM based PIM can realize more area-efficient implementation than t PIM.…”
Section: Introductionmentioning
confidence: 99%